Designing a Classifier Using Unsupervised Learning and Rough Set Theory - Gurusamy, Vairaprakash; Nandhini, K (International Journal of Computer Sciences and Engineering, 2025)
Dataset collected from multiple sources is often inconsistent and generates different label of decisions for the same conditional attribute values. A method for handling inconsistency has been proposed here using Kohonen Self organizing neural network, an unsupervised learning approach. After removing inconsistency, the minimum subset of attributes in the dataset called reducts are selected using Rough Set Theory, which effectively reduces dimensionality of the dataset. Unlike most of the existing reduct generation algorithms where all attributes are examined, here evaluation of all attributes is not required and therefore, time complexity has been improved considerably. In the next step, considering core attribute as root node of a decision tree, all possible rules are generated which are pruned based on information entropy and coverage of the rule set. The classifier is built using the reduced rule set demonstrating comparable results with the classifier consisting of all attributes.